The digital economy - Jordan, Tim 1959- (Polity, 2020)
"Tim Jordan deftly explores the workings of the trillion-dollar digital economy. He discusses the hype and significance surrounding its activities and practices in order to outline important concepts, theory, and policy questions. Rich with case studies, the book is an important reference for those getting to grips with this contemporary phenomenon"--